Inflammatory status in pediatric sickle cell disease: Unravelling the role of immune cell subsets - Marchesani, Silvio; Bertaina, Valentina; Marini, Olivia; Cossutta, Matilde; Di Mauro, Margherita; Rotulo, Gioacchino Andrea; Palma, Paolo; Sabatini, Letizia; Petrone, Maria Isabella; Frati, Giacomo; Monteleone, Giulia; Palumbo, Giuseppe; et al. (Frontiers in Molecular Biosciences, 2023)
Introduction: The mutation of the beta-globin gene that causes sickle cell disease (SCD) results in pleiotropic effects, such as hemolysis and vaso-occlusive crisis that can induce inflammatory mechanisms with deleterious consequences on the organism. Moreover, SCD patients display an increased susceptibility to infections. Few studies are currently available that evaluate a wide immunological profile in a pediatric population. This study proposes an evaluation of the immune profile in subjects with SCD in a pediatric population through a detailed analysis by flow cytometry. Methods and Materials: Peripheral blood samples from 53 pediatric patients with SCD (mean age 9.8 years, interquartile range 9 years) were obtained and then analyzed by flow cytometry, in order to evaluate changes in the immune populations compared to 40 healthy donors (mean age 7.3 years, interquartile range 9.5 years). Results: Our data showed an increase in neutrophils (with a reduction in the CD62L+ subpopulation) and monocytes (with a decrease in HLA-DRlow monocytes) with normal values of lymphocytes in SCD patients. In the lymphocyte subpopulations analysis we observed lower values of CD4+ T cells (with higher number of memory and central memory T lymphocytes) with increased frequency of CD8+ T cells (with a predominant naive pattern). Moreover, we observed higher values of CD39+ Tregs and lower HLA-DR+ and CD39- T cells with an increased Th17, Th1-17 and Th2 response. Conclusion: We observed immunological alterations typical of an inflammatory status (increase in activated neutrophils and monocytes) associated with a peculiar Treg pattern (probably linked to a body attempt to minimize inflammation intrinsic to SCD). Furthermore, we highlighted a T helper pathway associated with inflammation in line with other studies. Our data showed that immunological markers may have an important role in the understanding the pathophysiology of SCD and in optimizing targeted therapeutic strategies for each patient.